Cognition is not exceptional. (February 2018) - McGregor, Simon
Humans have a long history of insisting that they are members of a special group with some uniquely privileged characteristic and eventually being proved wrong. This has played out in cognitive science as in disciplines such as history or ethology. In this opinion piece, I spell out a position, here termed 'radical pancognitivism', that constitutes the polar opposite of cognitive exceptionalism, in that it attributes cognition to literally every physical system in the universe. My aim is not to persuade the reader that this view is correct, but rather to air it seriously for the benefit of discussion.